Periodontal conditions in a 7-19-year-old student population in Araraquara, São Paulo, Brazil, 1995 - Ercilia Leal Dini; Ana Lígia Rozato Foschini; Ioneide Maria Gomes Brandão
The Purpose of this study was to assess the periodontal conditions and treatment needs in 7-19-year-old Brazilian school children and adolescents enrolled in the urban public schools in Araraquara, São Paulo, Brazil, in 1995, to provide baseline data for monitoring changes in their periodontal status. A sample of 1,956 school children and adolescents aged 7 to 19 years was examined by two examiners previously calibrated using the CPITN (Community Pe riodontal Index of Treatment Needs). The results showed that bleeding was the most frequently observed periodontal condition in all age groups, with a mean of 3.0 sextants affected at age 15. The presence of calculus increased with age. In the 15-19-year age group, calculus and shallow pockets (3.5-5.5 mm) were observed in 39.8 per cent and 1.6 per cent of the adolescents, respectively. In order to achieve the WHO oral health goal of no more than one sextant scoring GPITN 1 (bleeding) or 2 (presence of dental calculus) at age 15, priority should be focused on primary prevention programs to benefit the periodontal health of the majority.